The Influence of Culinary Experience Quality and Local Food Authenticity on Word of Mouth with Memorable Tourism Experience on culinary tourism in Bandung City - Chaniago, Anggrany; Pahrijal, Rival; Arini, Rani Eka (Westscience Press, 2026)
This study aims to examine the influence of culinary experience quality and the authenticity of local food on word of mouth (WOM) and memorable tourism experiences (MTE) in the context of culinary tourism in Bandung. A quantitative approach was employed using data collected from 250 respondents who had participated in culinary tourism activities in Bandung. Data were gathered through a structured questionnaire using a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS-3). The results indicate that culinary experience quality and food authenticity both have significant positive effects on memorable tourism experiences and word of mouth. Additionally, memorable tourism experiences significantly influence word of mouth and act as a mediating variable in the relationship between culinary experience quality, food authenticity, and WOM. The model demonstrates strong explanatory power, with R² values of 0.682 for MTE and 0.741 for WOM. These findings highlight that high-quality and authentic culinary experiences not only enhance tourists’ memories but also encourage them to share positive experiences with others. This study contributes to the literature by integrating experiential and authenticity perspectives in culinary tourism research. Practically, the findings provide insights for tourism stakeholders in Bandung to enhance service quality, preserve culinary authenticity, and create memorable experiences to strengthen destination competitiveness and stimulate positive word of mouth.